Psychological Impact for Students in Carrying Out Online Learning During the Covid 19 Pademic: Literature Review - Trilia; Ayu Dekawaty; Inne Yelisni (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Background: Online learning is utilizing the internet, local, and networks platforms during the learning process to delivering teaching. Online learning has been considered positively by students, however, while it was started, plenty of students directly experienced difficulties The anxiety, stress, and even depression might rise as psychological impacts during online learning which lead to interference and affect the learning process Purpose: To review the students' psychological impact on online learning during the covid-19 pandemics. Methods: The literature review was used as an approach in this study. Database electronic was chosen from Google scholar, Science Direct, and PubMed. There were 8 articles that discussed the students' psychological impact on online learning during the covid-19 pandemic. Results: It found that the average psychological impact of students during the online learning process was anxiety (41 58%), stress (12.11%), and depression (3.68%) Conclusion: It has been shown that psychological impacts such as anxiety, stress, and even depression might interfere witn the education process.